GAMBARAN KECEMASAN IBU HAMIL TERHADAP RESIKO PENYAKIT COVID-19 DI WILAYAH KERJA PUSKESMAS MINAS - Winie Astari; Nike Puspita Alwi; Ainil Fitri (LPPM Universitas Abdurrab, 2023)
Pregnant women who experience anxiety during the Covid-19 pandemic cause fear and anxiety that have long-term effects on the health of pregnant women themselves. Psychological disorders that occur during pregnancy such as excessive anxiety will make fetal growth stunted and premature birth. Anxiety is worry, fear that has no clear cause, fear is caused by a threat, so that people will avoid themselves and so on. The purpose of this study was to describe the anxiety of pregnant women on the risk of Covid-19 at the Minas Public Health Center in 2021.The research method used is a simple descriptive design, the population that can be amounted to Â± 98 pregnant women and the sampling technique in the study using the total sampling technique with a sample of 98 pregnant women. The data collection method is by using a questionnaire.The results of this study indicate that the anxiety of pregnant women during the Covid-19 pandemic mostly experienced mild anxiety as many as 51 people (50.5%), 18 people were not anxious (20%) and 29 people had moderate anxiety (29.5%). ), because they are worried that the officers who help give birth do not use PPE (masks, fice shields and gloves), are afraid to leave the house and cannot afford nutritious food during Covid-19.